2021
DOI: 10.1101/2021.02.18.431905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light and noise pollution impacts specialist wildlife species disproportionately

Abstract: Global expansion of lighting and noise pollution alters how animals receive and interpret environmental cues. Yet we lack a cross-taxon understanding of how animal traits influence species vulnerability to this growing phenomenon. This knowledge is needed to improve the design and implementation of policies that mitigate or reduce sensory pollutants. We present results from an expert knowledge survey that quantified the relative influence of several ecological, anatomical, and physiological traits on the vulne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Even though comparable research found the light gathering ability explains nesting responses during the breeding season (Senzaki et al, 2020), in our study this trait was unrelated to changes in abundance of predominantly non‐breeding birds with respect to artificial night light. As such, rather than using anatomical traits, non‐breeding bird responses could be predicted by traits representing ecological sensitivities, such as activity patterns, trophic level, vagility, and habitat specializations (Ditmer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though comparable research found the light gathering ability explains nesting responses during the breeding season (Senzaki et al, 2020), in our study this trait was unrelated to changes in abundance of predominantly non‐breeding birds with respect to artificial night light. As such, rather than using anatomical traits, non‐breeding bird responses could be predicted by traits representing ecological sensitivities, such as activity patterns, trophic level, vagility, and habitat specializations (Ditmer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate how birds perceive and respond to noise, future research should test the relationship between intrinsic traits that represent anatomical and physiological sensitivities to sound. For example, in a survey that ranked the degree of traits impacting the survival, persistence and performance of a species, experts identified the ability to discriminate in noisy environments, auditory spectral resolution, and auditory bandwidth as the most plausible traits to predict vertebrate sensitivity to noise (Ditmer et al, 2021).…”
Section: Functional Traits Predicting Avian Response To Light and Noisementioning
confidence: 99%
“…for crepuscular species under ALAN such as insectivorous birds in urban environments [8]), whereas other species are experiencing a contracted temporal niche, such as nocturnal rodents that are only active under very dim conditions [9]. In both scenarios, the evolved traits that are adaptive under one temporal niche may now become maladaptive and result in a shift in the coevolutionary relationship between two species [10].…”
Section: Introductionmentioning
confidence: 99%